What is the reason to always perform intracytoplasmic sperm injection - ICSI? - Bisioli, Claudio (2018)
The use of intracytoplasmic sperm injection - ICSI without attending the findings from previous studies to the infertile couple has led to the indiscriminate use of this procedure in a significant number of clinics of reproductive medicine in the world. The present review analyses the reasons that led to this situation and raises possible answers or discussions to this proceeding.